Congenital Cytomegalovirus and Human Immunodeficiency Virus: Effects on Hearing, Speech and Language Development, and Clinical Outcomes in Children - Walsh, Hannah; Zuwala, Jillian; Hunter, Jessica; Oh, Yonghee (Frontiers in Pediatrics, 2021)
Prenatal infections can have adverse effects on an infant's hearing, speech, and language development. Congenital cytomegalovirus (CMV) and human immunodeficiency virus (HIV) are two such infections that may lead to these complications, especially when left untreated. CMV is commonly associated with sensorineural hearing loss in children, and it can also be associated with anatomical abnormalities in the central nervous system responsible for speech, language, and intellectual acquisition. In terms of speech, language, and hearing, HIV is most associated with conductive and/or sensorineural hearing loss and expressive language deficits. Children born with these infections may benefit from cochlear implantation for severe to profound sensorineural hearing losses and/or speech therapy for speech/language deficits. CMV and HIV simultaneously present in infants has not been thoroughly studied, but one may hypothesize these speech, language, and hearing deficits to be present with potentially higher severity. Early identification of the infection in combination with early intervention strategies yields better results for these children than no identification or intervention. The purpose of this review was to investigate how congenital CMV and/or HIV may affect hearing, speech, and language development in children, and the importance of early identification for these populations.